Ga and Ce ion-doped phosphate glass fibres with antibacterial properties and their composite for wound healing applications. Issue 44 (18th October 2019) - Łapa, Agata; Cresswell, Mark; Campbell, Ian; Jackson, Phil; Goldmann, Wolfgang H.; Detsch, Rainer; Parsons, Andrew; Ahmed, Ifty; Boccaccini, Aldo R.
Abstract : Soluble Ga/Ce-doped phosphate glass fibres exhibiting controlled release of ions were developed and characterised for wound healing applications. Fibres did not disturb the proliferation and migration of cells and showed antibacterial properties. Abstract : Novel gallium/cerium-doped phosphate glass fibres (PGF) were successfully manufactured by the melt-quenching and melt-spinning process. The amorphous character of the materials produced was confirmed using X-ray powder diffraction (XRD), and the elemental composition was investigated with X-ray fluorescence confirming the presence of 2 mol% of Ga2 O3 or CeO2 . Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of Q 1 and Q 2 structural phosphate species. Mechanical properties of the PGFs revealed tensile strength values of 428 ± 94 MPa and 379 ± 80 MPa, with elastic modulus values of 45 ± 4 GPa and 54 ± 9 GPa for Ce-PGF (diameter 25 μm) and Ga-PGF (diameter 18 μm), respectively. The influence of both dopants on the glass degradation properties was evaluated by tests in deionised water, which revealed a decreased dissolution rate for gallium-doped PGF in comparison to cerium-doped PGF. Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) measurements were used to explore ion release in cell culture medium, while ICP-mass spectrometry (ICP-MS) was used to measure ion release in deionised water. These techniques showed controlled release of therapeutic and antibacterial ions from the PGF. Antibacterial properties of Ce-PGF and Ga-PGF, based on turbidity measurements, were confirmed against Gram-positive bacteria. Moreover, Ce-doped phosphate glass fibres did not disturb the proliferation of human epidermal keratinocyte (HaCaT) cells or the mobility of mice embryonic fibroblasts (MEF). Applying an in vitro scratch assay showed full wound closure after 24 h of indirect incubation with Ga-PGF. Due to their superior processability as compared with Ga-PGFs, a fully degradable mesh based on Ce-PGF was designed and found to achieve high water uptake (up to 800%), suggesting its suitability for wound healing applications.